The Relationship Between Dietary Patterns and Stress and the Incidence of Gastritis at the Catherine Booth Clinic in Amurang - Tina Anjeli Lelet; A. A. J. Telew; L.L. Pongoh (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Gastritis, as one of the most common digestive health problems, affects all age groups, from adolescents to the elderly. Factors that trigger gastritis include eating patterns, smoking habits, coffee consumption, stress, and the use of NSAIDs (Nonsteroidal Anti-Inflammatory Drugs). In 2024, there were 204 patients who experienced gastritis, and from July to September 2025, there were 121 patients who experienced gastritis at the Catherine Booth Amurang Clinic. The purpose of this study is to determine the relationship between dietary patterns and stress with the incidence of gastritis at the Catherine Booth Amurang clinic. This research is a quantitative study using an analytical survey with a cross-sectional approach. This research was conducted at the Catherine Booth Clinic in Amurang, South Minahasa Regency, North Sulawesi, from May to October 2025. The population in this study consists of all outpatient patients at the Catherine Booth Clinic in Amurang from July to September 2025, totaling 3,184 people. The sample size is 100 people, selected using purposive sampling technique. The research instruments were questionnaires, and the data were analyzed using univariate and bivariate analysis with the Chi-Square test. The research results show a relationship between dietary patterns and the occurrence of gastritis (p value 0.000) and stress and the occurrence of gastritis (p value 0.000). Based on these results, it can be concluded that there is a relationship between dietary patterns and stress and the occurrence of gastritis.